Problematika Pembelajaran Bahasa Sunda Dimensi Linguistik dan Nonlinguistik - Opah Ropiah; Fahmi Rakhman; Fajar Sukma Nur Alam (Ranah: Jurnal Kajian Bahasa, 2023)
The purpose of this research is to find out the problems of learning Sundanese in linguistic and non-linguistic dimensions. The method used is a descriptive method with a qualitative research type. Sources of data in this study were the deputy head of curriculum, Sundanese language teachers, and class X students. Data collection techniques included observation, interviews, and documentation. The instruments used were stationery, interview guides, cell phones, and questionnaires. Data analysis using content analysis. The results of this study are 1) Problems of learning Sundanese language linguistic dimensions phonological errors in 72 cases with a percentage of 53.33%, syntactic errors in 75 cases with a percentage of 55.5%, syntactic errors in 80 cases with a percentage of 59.2, lexical errors -Semantic 20 cases with a percentage of 15%.; 2) The problems of learning Sundanese in the non-linguistic dimension have several obstacles in the implementation of the 2013 curriculum, the teacher's learning model is still monotonous, the teacher's understanding of IT is still lacking, the learning media is still limited, and there is still a lack of student interest and motivation in learning languages. AbstrakTujuan penelitian ini yaitu untuk mengetahui problematika pembelajaran bahasa Sunda dimensi linguistik dan nonlinguistik. Metode yang digunakan yaitu metode deskriptif dengan jenis penelitian kualitatif. Sumber data dalam penelitian yaitu wakil kepala sekolah bagian kurikulum, guru bahasa Sunda, dan siswa kelas X. Teknik pengumpulan data yaitu observasi, wawancara, dan dokumentasi. Instrumen yang digunakan yaitu alat tulis, pedoman wawancara, handphone, dan angket. Analisis data menggunakan analisis isi. Hasil penelitian ini yaitu: 1) Problematika pembelajaran bahasa Sunda dimensi linguistik terdiri dari kesalahan fonologi sebanyak 72 kasus dengan persentase 53,33%, kesalahan morfologi sebanyak 75 kasus dengan persentase 55,5%, kesalahan sintaksis 80 kasus dengan persentase 59,2%, dan kesalahan leksiko-semantis 20 kasus dengan persentase 15%; 2) Problematika pembelajaran bahasa Sunda dimensi nonlinguistik terdapat beberapa kendala dalam penerapan kurikulum 2013, model pembelajaran guru yang masih monoton, pemahaman guru terhadap IT masih kurang, media pembelajaran masih terbatas, dan masih kurangnya minat dan motivasi siswa dalam belajar kebahasaan.